Identifying Minority Ethnic Cultures Through Documentary Films: An Experimental Study on Vietnamese Students in Ho Chi Minh City - Truong Nguyen Khanh, Dan; Nguyen, Tan Khang; Nguyen Vo Huong, My; Lu Hoang Phuong, Thao; Tran Khanh, Van; Nguyen Thi Thao, Ly (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2025)
The preservation of ethnic minority cultures in Vietnam faces significant challenges due to globalization, modernization, and declining intergenerational cultural transmission. As traditional education struggles to sustain engagement, documentary films have emerged as a potential tool for cultural education. This study investigates the effectiveness of documentary films in enhancing Vietnamese students' awareness of H’mong and Hà Nhì cultures. Employing a mixed-method approach—including experiments, surveys, and focus group discussions—the research evaluates changes in students' knowledge and perceptions before and after exposure to documentary content. Results indicate that while documentaries enhance students’ understanding of both tangible and intangible cultural aspects, they are insufficient to promote active cultural preservation efforts. The study underscores the importance of integrating documentary films into higher education curricula alongside experiential learning and digital applications to foster deeper cultural engagement among young people.